Biased systematic and heuristic processing of politicians' messages: effects of source favourability and political interest of attitude judgment - Sungeun, Chung; Waheed, Moniza (University of Southern California, 2016)
This study investigated two information-processing modes for political messages from favored politicians: “biased” systematic processing and heuristic processing. In an experiment, college students (N = 183) with different levels of political interest received messages about unfamiliar political issues from either a favored or a less favored candidate in the 2008 U.S. presidential election. For those with low levels of political interest, source favorability had a direct effect on attitudes, indicating heuristic processing. For those with high political interest, source favorability had an indirect effect on attitudes through message-relevant thoughts, indicating biased systematic processing. Theoretical and practical implications of the findings are discussed.